PENGARUH IKLAN, FASILITAS, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PERUMAHAN GRIYA ZAFIRA PERMAI BREBES - Sulistia Ameliyanti; Andi Yulianto; Azizah Indriyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research was to determine the influence of advertising, facilities and service quality on purchasing decisions at the Griya Zafira Permai Brebes housing complex. The type of research carried out by researchers uses casual associative research using a quantitative approach. The sample taken to represent the population was 109 customers. Analysis techniques in testing multiple linear regression analysis, using the SPSS version 25.0 program. Based on the test results, it shows that the significant value of the advertising variable (X1) is 0.026 > 0.05 and the calculated t value is (2.263) > t table (1.983). The significant value of the facility variable (X2) is 0.035 > 0.05 and the calculated t value is (2.140) > t table (1.983). Meanwhile, the significant value of the service quality variable (X3) is 0.001 > 0.05 and the calculated t value is (3.482) > t table (1.983), which means it influences purchasing decisions. Taken together, advertising, facilities and service quality have a significant influence on purchasing decisions at Griya Zafira Permai